2012
DOI: 10.1128/jvi.00446-12
|View full text |Cite
|
Sign up to set email alerts
|

Genome, Integration, and Transduction of a Novel Temperate Phage of Helicobacter pylori

Abstract: Helicobacter pyloriis a common human pathogen that has been identified to be carcinogenic. This study isolated the temperate bacteriophage 1961P from the lysate of a clinical strain ofH. pyloriisolated in Taiwan. The bacteriophage has an ico… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
51
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(55 citation statements)
references
References 48 publications
1
51
1
2
Order By: Relevance
“…Several bacteriophages (phages) of H. pylori have been reported (4,5,9,12). In general, phages are considered to contribute to bacterial evolution and may affect host features, such as biological behavior, pathogenesis, or adaptation, via their possible roles in horizontal gene transfer and bacteria-phage antagonistic coevolution (4,5,7).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Several bacteriophages (phages) of H. pylori have been reported (4,5,9,12). In general, phages are considered to contribute to bacterial evolution and may affect host features, such as biological behavior, pathogenesis, or adaptation, via their possible roles in horizontal gene transfer and bacteria-phage antagonistic coevolution (4,5,7).…”
mentioning
confidence: 99%
“…In general, phages are considered to contribute to bacterial evolution and may affect host features, such as biological behavior, pathogenesis, or adaptation, via their possible roles in horizontal gene transfer and bacteria-phage antagonistic coevolution (4,5,7). In this study, to extend our understanding not only of the H. pylori phages themselves but also of the process of coevolution of H. pylori and its phages, phages KHP30 and KHP40 were isolated from the culture supernatants of East Asian-type isolates from Japanese patients living in distinct geographic regions, and their complete genomic sequences were determined.…”
mentioning
confidence: 99%
“…In fact, an evolutionary link between a prophage and differentiation in B. subtilis has been suggested, howeverthe underlying mechanisms and associated factors are still not fully understood (Lewis et al, 1998;Luo et al, 2012). Besides this, the mutations shifting the balance from lysogeny to lysis have also been suggested as a cause of autoplaque phenomenon (Bednarz et al, 2014).…”
Section: Issn: 2319-7706 Volume 6 Number 9 (2017) Pp 32-46mentioning
confidence: 99%
“…In fact, in some bacteria, the autoplaque forming phages show a narrow host range and serve as a vehicle to specifically drive genetic diversification of the bacterial host (Luo et al, 2012). Further, the release of DNA due to autolysis serves as a raw material to drive transformation and evolution of bacterial population and minimize the accumulation of damages DNA or mutations (Redfield, 1988).…”
Section: Issn: 2319-7706 Volume 6 Number 9 (2017) Pp 32-46mentioning
confidence: 99%
“…This diversity can be attributed to altered DNA repair, elevated mutation rates, high frequency of intraspecific recombination, chromosomal DNA transfer events from other species, incorporation of naked DNA from the environment, plasmid mobilization, and integration of acquired DNA in the so-called plasticity zones [4,[8][9][10]. In addition, the presence of phages has been described for several H. pylori strains, acting as another source of bacterial diversity and evolution [11][12][13][14][15]. Using newly developed bioinformatics programs, recent comparative studies of 29 complete genome sequences of strains from different parts of the world revealed a high-resolution picture of the H. pylori population structure as well as the extent and direction of genetic flux between subgroups of the bacterium [16].…”
Section: Introductionmentioning
confidence: 99%